PRESEPSIN AND PROCALCITONIN VALUES TO DETERMINE THE PROGNOSIS OF UROSEPSIS - Addin, Sofyan Rais; Djojodimedjo, Tarmono; Rizaldi, Fikri (Indonesian Urological Association, 2018)
Objective: To evaluate the prognostic value of presepsin and procalcitonin in patient with urosepsis. Material & Method: This is an observational prospective study. Patients who fulfilled the criteria for urosepsis at Soetomo Hospital Surabaya were enrolled. Presepsin and procalcitonin were measured at first admission. All patients were managed according to standard urosepsis therapy. At the 28th day of treatment, patients were evaluated and classified into survivor and non-survivor. The statistical analysis were tested with logistic regression test using software SPSS 23. Results: 30 urosepsis patients were included in this study with average age was 48.3 years (range 21-77 years). There were 23 survivor and 7 non-survivor. Mean presepsin values were higher in non-survivor than in survivor but the difference was not significant (4405 ± 4664 vs 4042 ± 2643, p=0.259). Mean procalcitonin value was significantly higher in non-survivor than in survivor (7.68 ± 6.81 vs 3.27 ± 2.74, p=0.013). Using the cut off value ≥2.24 ng/ml, procalcitonin can predict mortality in 28 days with sensitivity 71.4% and specificity 47.8%. Conclusion: Presepsin can not be used to determine the prognosis of urosepsis patients. Procalcitonin showed a significant correlation with outcome of urosepsis patients so it can be use to determine the prognosis of urosepsis.